Pain level after ACL reconstruction: A comparative study between free quadriceps tendon and hamstring tendons autografts - Cristian Tudor Buescu; Adela Hilda Onutu; Dan Osvald Lucaciu; Adrian Todor (Acta Orthopaedica et Traumatologica Turcica)
Objective: The objective of this study was to compare the pain levels and analgesic consumption after single bundle ACL reconstruction with free quadriceps tendon autograft versus hamstring tendon autograft. Patients and methods: A total of 48 patients scheduled for anatomic single-bundle ACL reconstruction were randomized into two groups: the free quadriceps tendon autograft group (24 patients) and the hamstring tendons autograft group (24 patients). A basic multimodal analgesic postoperative program was used for all patients and rescue analgesia was provided with tramadol, at pain scores over 30 on the Visual Analog Scale. The time to the first rescue analgesic, the number of doses of tramadol and pain scores were recorded. The results within the same group were compared with the Wilcoxon signed test. Results: Supplementary analgesic drug administration proved significantly higher in the group of subjects with hamstring grafts, with a median (interquartile range) of 1 (1.3) dose, compared to the group of subjects treated with a quadriceps graft, median = 0.5 (0.1.25) (p = 0.009). A significantly higher number of subjects with a quadriceps graft did not require any supplementary analgesic drug (50%) as compared with subjects with hamstring graft (13%; Z-statistics = 3.01, p = 0.002). The percentage of subjects who required a supplementary analgesic drug was 38% higher in the HT group compared with the FQT group. Conclusion: The use of the free quadriceps tendon autograft for ACL reconstruction leads to less pain and analgesic consumption in the immediate postoperative period compared with the use of hamstrings autograft. Level of Evidence: Level I Therapeutic study Keywords: ACL reconstruction, Pain, Hamstring tendons, Free quadriceps tendon